Some Guidelines to Publish Open Education Resource (OER) Materials for ADA Auditory Compliance in a Business Class - Kohli, Raj K; Pant, Anurag (Archives of Business Research, 2024)
The number of persons with disabilities in the US has steadily increased to more than one in four today. Such disabilities have impaired both physical and cognitive functioning in human beings. Educational designers have suggested using a universal approach to designing courses and their materials such that all students could potentially benefit from such accommodations. Visual disability in particular has caused persons to be unable to grasp materials fully due to their dependence on text to speech software. Persons with disability have lagged the rest of the population in employability because of their lack of access to proper materials. In business education, finance classes have a particular problem of being able to depict tabular information to those with visual disability. This paper provides one method of how text-to-speech options can be used to suitably modify teaching materials and enable better learning among those with visual challenges.